Respon Otonom Terhadap Penggunaan Masker Pada Individu Dengan Gangguan cemas - Adrianus Kosasih; Erita Istriana; Verawati Sudarma; Rita Khaerani; Henie Widowati (Fakultas Kedokteran Universitas Trisakti, 2026)
Background Medical masks, commonly known as surgical masks, are designed to inhibit the spread of microorganisms. While masks offer numerous benefits, they also have side effects, including anxiety. N95 respirators have several additional side effects compared to surgical masks. This study aimed to examine the relationship between N95 mask use and autonomic responses in individuals with anxiety disorders, a relatively understudied area. Methods This is an analytic experimental study on 140 respondents. Assessment of anxiety disorders was carried out by completing the DASS-42 questionnaire and psychiatric interviews by a psychiatrist. Autonomic responses are assessed using heart rate variability (HRV), the fluctuation in the time intervals between adjacent heartbeats. Short-term root mean square of successive differences (RMSSD) HRV parameters were measured using the Polar H10. HRV was measured when the respondent was not wearing a mask, when wearing an N95 mask, and when wearing an N95 mask with a valve opened (sham). Results HRV in respondents with anxiety disorders had a significantly lower value than in respondents non-anxiety disorders. HRV values were significantly lower in respondents with anxiety disorders compared to those without, both at baseline (median: 16.33 vs 23.35, p=0.004), while using an N95 mask (median: 16.47 vs 22.01, p=0.008), and while using a sham N95 mask (median: 16.94 vs 22.24, p=0.005). However, there was no relationship between the use of N95 masks and HRV in respondents with anxiety disorders (RMSSD baseline vs. N95: median 16.33 vs. 16.47, p=0.979). Conclusions There is no relationship between the use of N95 masks and HRV in individuals with anxiety disorders. These findings suggest that N95 use is safe even for individuals with anxiety disorders.